Lymphotoxin-α Gene 252G Allelic Variant Is a Risk Factor for Large-Vessel-Associated Ischemic Stroke - Szolnoki, Zoltán; Havasi, Viktória; Talián, Gábor; Bene, Judit; Komlósi, Katalin; Somogyvári, Ferenc; Kondacs, András; Szabó, Mihály; Fodor, Lajos; Bodor, Anita; Melegh, Béla (Journal of molecular neuroscience, 2005)
A direct role of lymphotoxin-alpha (LTA) in promoting atherosclerotic plaque growth has been demonstrated recently. The different protein transcripts of the naturally occurring genetic variants of the LTA gene have been demonstrated to exhibit affected functions, and an allelic difference in binding to transcription factor(s) has also been suggested. The homozygous variant of LTA characterized by the intron 1 252A-->G (252G) transition, which naturally coexists with an exon 3 804C-->A (804A) single-nucleotide polymorphism (SNP), has been reported as a susceptibility gene for myocardial infarction. Because the atherosclerotic process is also an integral component in the pathogenesis of certain types of vascular stroke, we investigated the possible significance of the above SNPs in 353 ischemic stroke patients and 180 healthy controls. The homozygous LTA allele with the 252G and 804C SNPs occurred more frequently in stroke patients (13.9%) than in controls (7.20%, p<0.025). Specific subclassification of the patients revealed an accumulation of these SNPs in large-vessel, pathology-associated cerebral infarction (18.2%); multivariate logistic regression analysis of the data confirmed this association, with an odds ratio of 2.1 (95% confidence interval, 1.3-6.2; p<0.005). Elimination of all subjects with a history or evidence of ischemic heart disease, including myocardial infarction, did not affect this association. These data show that besides the role in the development of myocardial infarction, the homozygous carriage of the LTA allele with 252G and 804A SNPs is a novel susceptibility factor for largevesselassociated ischemic stroke.